High Fluoride Ingestion Impairs Bone Fracture Healing by Attenuating M2 Macrophage Differentiation - Du, Chengcheng; Xiao, Pengcheng; Gao, Shengqiang; Chen, Shengwen; Chen, Bowen; Huang, Wei; Zhao, Chen (Frontiers in Bioengineering and Biotechnology, 2022)
Fluorosis is still endemic in at least 25 countries around the world. In this study, we investigated the effect of high fluoride intake on fracture healing. Our in vitro experiments found that fluoride inhibited the osteogenic and angiogenic differentiation of MSCs in a dose-dependent manner. By constructing a bone fracture model, we found that high fluoride intake influences bone fracture by attenuating endochondral ossification and angiogenesis. In the mechanism, we clarified that high fluoride inhibits M2 differentiation rather than M1 differentiation in the fracture area, which may contribute to the delayed healing of the fracture. These findings provide an essential reference for the clinical treatment of bone fracture patients with a history of high fluoride intake or skeletal fluorosis patients.